Early variation of ultrasound halo sign with treatment and relation with clinical features in patients with giant cell arteritis. (11th May 2020) - Ponte, Cristina; Serafim, Ana Sofia; Monti, Sara; Fernandes, Elisabete; Lee, Ellen; Singh, Surjeet; Piper, Jennifer; Hutchings, Andrew; McNally, Eugene; Diamantopoulos, Andreas P; Dasgupta, Bhaskar; Schmidt, Wolfgang A; et al.
Abstract: Objectives: To compare the ultrasound characteristics with clinical features, final diagnosis and outcome; and to evaluate the halo size following glucocorticoid treatment in patients with newly diagnosed GCA. Methods: Patients with suspected GCA, recruited from an international cohort, had an ultrasound of temporal (TA) and axillary (AX) arteries performed within 7 days of commencing glucocorticoids. We compared differences in clinical features at disease presentation, after 2 weeks and after 6 months, according to the presence or absence of halo sign. We undertook a cross-sectional analysis of the differences in halo thickness using Pearson's correlation coefficient ( r ) and Analysis of Variance (ANOVA). Results: A total of 345 patients with 6 months follow-up data were included; 226 (65.5%) had a diagnosis of GCA. Jaw claudication and visual symptoms were more frequent in patients with halo sign ( P =0.018 and P =0.003, respectively). Physical examination abnormalities were significantly associated with the presence of ipsilateral halo ( P <0.05). Stenosis or occlusion on ultrasound failed to contribute to the diagnosis of GCA. During 7 days of glucocorticoid treatment, there was a consistent reduction in halo size in the TA (maximum halo size per patient: r =−0.30, P =0.001; and all halos r =−0.23, P <0.001), but not in the AX ( P >0.05). However, the presence of halo at baseline failed to predict future ischaemic events occurring during follow-up. Conclusion: In newly diagnosed GCA, TA halo is associated with the presence of ischaemic features and its size decreases following glucocorticoid treatment, supporting its early use as a marker of disease activity, in addition to its diagnostic role.